Improvement of dispersion of different carbon nanotubes (CNTS) in liquid polymer resin for composites - Beg, M. D.H.; Yunus, Rosli Mohd; Bijarimi, Mohd (2017)
This research presents a non-destructive modification of multi-walled carbon nanotube (MWCNT) and fabrication of MWCNT reinforced unsaturated polyester resin (UPR) nanocomposite. In this work, pre-dispersion of MWCNTs was performed in the tetra hydro furan (THF) solvent. In addition, pre-dispersion and post- dispersion time was optimized as 1.5 hour and 2 hour, respectively. The pre-dispersed MWCNT reinforced UPR (THF-MWCNT-UPR) nanocomposite exhibited better properties as compared to directly dispersed MWCNT reinforced UPR (MWCNT-UPR) nanocomposite. The optimum amount of MWCNT was evaluated through mechanical properties of nanocomposites contained 0.05 to 0.5 wt% MWCNT. The experimental tensile modulus (TM) of 0.3 wt% MWCNT reinforced 0.3CNT-UPR nanocomposite linearly fitted with Halpin –Tsai equation. Therefore, 0.3 wt% MWCNT was suggested as the optimum quantity. The nondefect modification of MWCNT was carried out with hyper branched polyester (HBP) and shellac (SL) functional polymers. The structural and thermal properties of 10 wt% HBP and SL coated HBCNT and SLCNT was noticeably improved as compared to pristine MWCNT. Moreover, 10 wt% HBP and SL coated HBCNT and SLCNT nanotubes remarkably reduced the curing temperature of nanosuspensions. Therefore, 10 wt% was considered as the optimum amount of HBP and SL to modify MWCNT. Optimum HBP coated MWCNT incorporated (OHBPCNT-UPR) nanocomposite became stiff. Conversely, optimum SL coated MWCNT incorporated (OSLCNT-UPR) nanocomposite became tough as compared to MWCNT reinforced nanocomposite. Different ratios of HBCNT and hydroxyl (OH) functionalized MWCNT (OHCNT) were incorporated in UPR to fabricate hybrid (HBOHCNT-UPR) nanocomposites. The ratio of HBCNT and OHCNT was optimized as 2:1 through the curing behavior of hybrid nanosuspensions. The comparative study was carried out among non-covalent and covalent functionalized as well as hybrid MWCNT reinforced UPR nanocomposites. Hybrid MWCNT incorporated nanosuspension exhibited the lowest curing temperature as compared to non-covalent and covalent functionalized MWCNT incorporated nanosuspensions. The hybrid nanocomposite exhibited the highest stiffness among nanocomposites which was individually fabricated with HBCNT and OHCNT. The mixture of non-covalent functionalized and covalent functionalized MWCNT jointly reinforced the properties of UPR. From this research 5 journal and 3 conference papers has been published.